Tuberculosis preventive chemotherapy in the HIV infected in the regions of the Russian Federation with high prevalence of HIV infection - E. B. Tsybikova (Tuberkulez i Bolezni Lëgkih, 2016)
In 2014 in 18 regions of the Russian Federation with the high prevalence of HIV infection the part of HIV patients covered by tuberculosis preventive chemotherapy was extremely small making 5.8% out of the total number. And the part of children and adolescents in the age from 0 to 17 years old made only 1.8%. Only in 6 out of 18 Russian regions the preventive tuberculosis chemotherapy was conducted among new HIV patients. In 15 Russian regions among HIV infected children and adolescents in the age from 0 to 17 years old no preventive tuberculosis chemotherapy was done.